2017
DOI: 10.1111/cup.12871
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lymphomatoid papulosis with follicular mucinosis: a clinicopathologic study of 3 cases with literature review and conceptual reappraisal

Abstract: Lymphomatoid papulosis (LyP), characterized by recurring, waxing and waning, cutaneous papulonodules, is increasingly recognized to represent a heterogeneous collection of pathologically dissimilar subtypes. Recently, a follicular LyP variant was proposed, featuring folliculotropism. Folliculotropism by atypical lymphocytes is conventionally associated with follicular mucinosis and mycosis fungoides (MF), and review of the literature suggests co-occurrence of folliculotropism and follicular mucinosis in LyP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Rarely, primary cutaneous CD30‐positive lymphoproliferative disorders have been reported to exhibit FM on pathology. Lymphomatoid papulosis may rarely exhibit folliculotropism and FM 29‐31 . Distinction from FMF rests on the clinical correlation along with the presence of large atypical CD30‐positive cells.…”
Section: Secondary Follicular Mucinosismentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, primary cutaneous CD30‐positive lymphoproliferative disorders have been reported to exhibit FM on pathology. Lymphomatoid papulosis may rarely exhibit folliculotropism and FM 29‐31 . Distinction from FMF rests on the clinical correlation along with the presence of large atypical CD30‐positive cells.…”
Section: Secondary Follicular Mucinosismentioning
confidence: 99%
“…Lymphomatoid papulosis may rarely exhibit folliculotropism and FM. [29][30][31] Distinction from FMF rests on the clinical correlation along with the presence of large atypical CD30-positive cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…The finding of FM in primary cutaneous CD30+ LPD is unusual and 6 cases have been reported in the literature so far and were initially misdiagnosed as folliculotropic MF. 28 FM has been reported also in the setting of cutaneous lesions of adult T-cell leukemia lymphoma 29 . In our study we report four additional cases of CD30+ LPD with FM as well as CD4+ small/ medium CTCL and cutaneous peripheral T-cell lymphoma, unspecified, suggesting that the presence of FM in CTCL types other than MF may not be a rare condition as previously thought.…”
Section: Resultsmentioning
confidence: 94%
“…In human medicine, FM is considered a tissue reaction pattern and not a disease per se 3. It can be observed in many different inflammatory and neoplastic diseases, most classically associated with folliculotropic lymphoma, lymphoproliferative disorders and haematological malignancies, and less commonly with ADRs 4 8–10…”
Section: Discussionmentioning
confidence: 99%
“…In NPDs, an immunological pathogenesis in a genetically predisposed breed is suggested 2. In human beings, FM is associated frequently with cutaneous lymphoma and infrequently with inflammatory disorders, such as drug reactions 3 4. This case is, to the best of the authors’ knowledge, the first reported in a dog experiencing long‐term remission without treatment and for which a possible adverse drug reaction (ADR) to the deslorelin implant was suspected.…”
Section: Introductionmentioning
confidence: 86%